When a "classic" illustrates the classics. Jean Claverie and the tales of Perrault - Connan-Pintado, Christiane (Ondina - Ondine, 2023)
Abstract In response to a publishing commission or, more rarely, to a personal intention, the artists of the album are confronted with heritage works whose reading they renew by their illustrations. This is the phenomenon that we propose to approach from the illustration of the Tales of Perrault by Jean Claverie. Many criteria allow us to classify this artist of the album in the category of the "classics" of the genre: his legitimization by prestigious prizes, by the school institution, by university critics; the Centre de l'illustration de Moulins, opened in 2005, devoted a monographic exhibition to him the following year.The illustration of tales occupies a central place in his work which began in 1977 with the legend of the Pied Piper of Hamelin. Initially eclectic - Bechstein, Grimm, Andersen, Wilde, Beck - he later showed a real predilection for Perrault, of which he illustrated six tales. While placing them in their context, Jean Claverie manages to make them close to us by humanizing their characters. Faithful to his personal style, he embraces the spirit of the heritage author whose "playful narration" and facetiousness he iconographically mimics, because he knows how to target, like him, a double audience.Key words: classic, album, legitimization,  illustration, Perrault tales.